Rancang Bangun Sistem Informasi Inventory pada "Happy Mart" Menggunakan Metode EOQ - Hestiara Sinta; Syefrida Yulina (ABEC Indonesia, 2023)
An inventory information system is a system that functions to find out the inventory of goods in warehouses that are used or developed with various technologies. The Happy Mart store does not yet have an inventory information system, where currently the management of inventory in the warehouse is still done manually, and the recording of inventory is still stored in the general ledger. Therefore, the Happy Mart store requires an inventory management system in the warehouse so that inventory management and recording at the Happy Mart store can run efficiently. This system is built based on a website and applies the Economic Order Quantity (EOQ) calculation method to determine the optimal number of goods ordered. This research has conducted black box testing with the results of the system in accordance with the specifications and requirements, user acceptance testing with the results of this system can help the store manage goods and be able to manage relevant reports and data for future business decision making, and usability testing with an overall result of 94%, which means that this system is easy to understand and easy to understand by users so that users feel satisfied with the system being built. Keywords: black box testing, Economic Order Quantity (EOQ), inventory information system, User Acceptance Test (UAT), Usability Testing.